Two to Tango : An Evaluation of World Bank Group Support to Fostering Regional Integration - Independent Evaluation Group (World Bank, Washington, DC, 2019)
This evaluation assesses the Bank Group’s effectiveness and comparative advantage in fostering regional integration during FY2003–17 and draws lessons that can be used to inform future regional integration operations. Client countries of the World Bank Group have turned to regional integration as one of the pathways toward faster economic development and peace, and to help overcome development challenges. Main findings of the report include: (i) Overall, the Bank Group’s efforts to foster regional integration have led to mostly positive development outcomes in the Sub-Saharan Africa Region and in infrastructure sectors. (ii) Though the IDA Regional Window program has also contributed to regional integration (mainly in the Africa Region), the development outcomes of its interventions are not significantly different from similar projects co-financed outside the program.